Health and health-related indicators in slum, rural, and urban communities: a comparative analysis. Issue 1 (1st December 2016) - Mberu, Blessing U.; Haregu, Tilahun Nigatu; Kyobutungi, Catherine; Ezeh, Alex C.
Abstract : Background: It is generally assumed that urban slum residents have worse health status when compared with other urban populations, but better health status than their rural counterparts. This belief/assumption is often because of their physical proximity and assumed better access to health care services in urban areas. However, a few recent studies have cast doubt on this belief. Whether slum dwellers are better off, similar to, or worse off as compared with rural and other urban populations remain poorly understood as indicators for slum dwellers are generally hidden in urban averages. Objective: The aim of this study was to compare health and health-related indicators among slum, rural, and other urban populations in four countries where specific efforts have been made to generate health indicators specific to slum populations. Design: We conducted a comparative analysis of health indicators among slums, non-slums, and all urban and rural populations as well as national averages in Bangladesh, Kenya, Egypt, and India. We triangulated data from demographic and health surveys, urban health surveys, and special cross-sectional slum surveys in these countries to assess differences in health indicators across the residential domains. We focused the comparisons on child health, maternal health, reproductive health, access to health services, and HIV/AIDS indicators. Within each country, we compared indicators for slums with non-slum, city/urban averages, rural, and national indicators. Between-country differences were also highlighted. Results: In all the countries, except India, slum children had much poorer health outcomes than children in all other residential domains, including those in rural areas. Childhood illnesses and malnutrition were higher among children living in slum communities compared to those living elsewhere. Although treatment seeking was better among slum children as compared with those in rural areas, this did not translate to better mortality outcomes. They bear a disproportionately much higher mortality burden than those living elsewhere. Slum communities had higher coverage of maternal health services than rural communities but it was not possible to compare maternal mortality rates across these residential domains. Compared to rural areas, slum communities had lower fertility and higher contraceptive use rates but these differences were reversed when slums were compared to other urban populations. Slum–rural differences in infant mortality were found to be larger in Bangladesh compared to Kenya. Conclusion: Mortality and morbidity indicators were worse in slums than elsewhere. However, indicators of access to care and health service coverage were found to be better in slums than in rural communities.